Philosophy in Safavid Iran (Leiden)
ix, 384 sayfa
Keywords: “This edited volume offers new insights into the philosophical milieu of late Safavid Iran (1062-1148/1652-1736). Moving beyond the celebrated figures of Mīr Dāmād (d. 1041/1631) and Mullā Ṣadrā (d. 1045/1636), it explores the often-overlooked thinkers and ideas that sustained philosophical inquiry in the later Safavid period. The chapters provide detailed studies of the lives, works, and doctrines of eight major philosophers, revealing the richness and diversity of late Safavid thought. The introduction situates these contributions within their broader intellectual context, tracing the themes and developments that shaped the era's philosophical discourse.“ --